Research of Economic Burdens Linked to Physical Inactivity - Paár Dávid (REGIONAL AND BUSINESS STUDIES, 2011)
ABSTRACT Interest in monitoring the living standards has gradually risen in our country in recent years. The National Development Plan’s main goal was to increase living standards for the domestic population in the period between 2004 and 2006. Unfortunately, it couldn’t reach its goal, and the Hungarian indicators’ scores fall at the end of European ranking list, according to the WHO report of May 2010. The result of Eurobarometer’s representative case of 2010 is depressing, showing that 77% of the population is physically inactive. This paper’s objective was to produce numerical data of the economic burdens in sick-pay, furthermore to measure the costs could be saved in sick-pay with a decrease of physical inactivity. We have used national and international studies, reports, and methodologies in our research. We have accessed sources in the database of National Health Insurance Fund Administration, and created our own questionnaire (n=1158). On conclusions indicate that it is the responsibility of the decision-makers, to take action to decreasing the physical inactivity so as to spare drastic expenses every year. Keywords: physical inactivity, lifestyle, economic burdens, sick-pay allowances,